ANALYSIS EFFECT OF PRICE, SERVICE QUALITY AND MARKETING RELATIONSHIP ON REPURCHASING INTEREST WITH CUSTOMER SATISFACTION AS INTERVENING VARIABLE IN CV. BEKASI UNGGAS - Kristianto, Ardy; Sawitri, Ni Nyoman; Achmad Harianto, Raden (Dinasti Publisher, 2022)
The research aims to determine the effect of price, service quality and marketing relationship on repurchase intention with customer satisfaction as an intervening variable at CV. Bekasi Unggas. The type of research used is quantitative research. The data presented in this research was obtained through a questionnaire given to 53 respondents who as a customer at CV. Bekasi Unggas. Research design used is hypothesis testing using the structural equation model (SEM) – Smart PLS version 3.3.3. Results from this research show that: (1) There is a direct effect of price, marketing relationship and consumer satisfaction on repurchase intention, (2) There is no evidence of a direct effect of service quality on repurchase intention, (3) There is an indirect effect price, service quality and marketing relationship on repurchase intention through customer satisfaction.